The forever prisoner : the full and searing account of the CIA's most controversial covert program - Scott-Clark, Cathy, 1965-; Levy, Adrian, 1965- (Atlantic Monthly Press, 2022)
"Six months after 9/11, CIA and FBI agents captured Abu Zubaydah, mistakenly believed to be number three in the Al Qaeda hierarchy. Frantic to thwart a much-feared second attack, the U.S. rendered him to a black site in Thailand. There he collided with Air Force psychologist James Mitchell. Believing that Abu Zubaydah had been trained to resist interrogation, Mitchell and others were authorized to use brutal interrogation techniques that would have violated the Geneva Conventions, international rules and treaties, and U.S. law had not government lawyers rewritten the human rights rulebook. The program metastasized over seven years, encompassing dozens of prisoners and multiple black sites. Ultimately, the U.S. Senate judged it was torture. As a result, numerous prisoners, including Abu Zubaydah, remain in Guantánamo, never charged with any crimes because their trial would reveal the extreme brutality they endured. Based on four years of intensive reporting around the world, on multiple interviews with key protagonists on all sides who speak candidly for the first time, and on thousands of previously classified documents recently released by FOIA requests, The Forever Prisoner is a powerful chronicle of a shocking government initiative that in the end produced zero high-value intelligence, continues to influence U.S. policy to this day, and remains in the headlines twenty years after its inception. It is also a primary source for a feature-length documentary of the same title by Academy Award winner Alex Gibney to debut on HBO on December 6, 2021. Held incommunicado for twenty years, Abu Zubaydah speaks for the first time in the pages of The Forever Prisoner"--